The Effect Propioceptive Training on Ladder Drill Training Variation in Dynamic Balance of Futsal Players - Maulidia Risma Hanani; Primayanti, I Dewa Ayu Inten; Lesmana, S. Indra (PT Inovasi Pratama Internasional, 2024)
Futsal is a multidirectional sport requiring players to move dynamically, it needs dynamic balance to create good performance. The combination of proprioceptive training interventions to ladder drill variations can affect dynamic balance for futsal players. This research method uses a pretest- posttest two group design. The research sample consisted of 30 people with 15 people in each group. Group 1 was given proprioceptive training and ladder run training, while group 2 was given proprioceptive training and ladder jump training. Dynamic balance measurement with Y balance test. The results of average test on dynamic balance variable, the results of paired sample t test showed differences in pretest and posttest values, group 1 (95.8 ± 4.4) with ( p = 0.00) while group 2 ( 98.2 ± 3.8) with ( p = 0.000). The results of the independent t test with a value of ( p = 0.127). The conclusion of this study is the combination of proprioceptive training and ladder run training interventions is as well as proprioceptive training and ladder jump training for dynamic balance of futsal players.